Multiple Bony Injuries on Bone Scan in a Case of Unsuspected Child Abuse. (27th June 2017) - Chuang, Ya-Wen; Hsu, Chien-Chin; Chang, Chin-Chuan; Lin, Chia-Yang; Chu, Hsiu-Lan; Huang, Ying-Fong; Tyan, Yu-Chang
Abstract : This case is described of an eleven-month-old infant with lower limbs swelling and the left elbow skeletal malformation following a fall. The radionuclide bone scan was performed to exclude bone infection or congenital skeletal anomaly. The images unexpectedly showed multiple increased radioactive foci throughout the whole body. It was a strong probability of child abuse. All lesions are readily apparent on the following plain film radiographs and MRI.